Single Versus Multiple Dose Regimen of Prophylactic Antibiotic in Cesarean Section - Bhattachan, K; Baral, GN; Gauchan, L (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: The purpose of this study was to compare the efficacy of single combined dose of Cefotaxime and Metronidazole against conventional regimen of Ampicllin and Metronidazole for five days for the prevention of infectious morbidities in cesarean deliveries. Methods: This study was carried out at Paropakar Maternity and Women’s Hospital, Kathmandu from April to August 2011. Hundred patients, who had cesarean deliveries for various indications, were divided into two groups with fifty on each arm. Patients in group I were treated with intravenous single dose of Cefotaxime and Metronidazole after cord clamping, whereas those patients in group II were treated with Ampicillin and Metronidazole for five days. Efficacy of the treatment was compared in terms of postoperative infectious morbidities, duration of hospital stay and cost of antibiotics. Results: Overall ten cases (10%) had post-operative complications in which eight (8%) had infectious and two (2%) had thrombophlebitis. The infectious morbidities were febrile morbidities in four cases (4%) followed by urinary tract infection in three cases (3%) and wound infection in one case (1%). There was no statistically significant difference among distribution of these morbidities and in the mean duration hospital stay. The cost of single dose regimen was one-eighth of the multiple dose regimens which was statistically significant (p=0.000). Conclusions: Single dose of Cefotaxime and Metronidazole was equally effective as multiple doses of Ampicllin and Metronidazole for five days in prevention of infectious morbidities with benefit of cost. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 50-53 DOI: http://dx.doi.org/10.3126/njog.v8i2.9771